Acetohydroxamic acid as inhibitor of potato poliphenoloxidase - Portela, Fábio (Pesquisa Agropecuaria Brasileira, 2014)
This research was conducted aiming to determine the inhibitory effect of the acetohydroxamic acid as an enzyme inhibitor on isolated polyphenoloxidade (E.C. 1.14.18.1, monophenol monooxygenase). The results indicate this acid as a noncompetitive inhibitor of this enzyme.